Decreased haemodynamic response and decoupling of cortical gamma-band activity and tissue oxygen perfusion after striatal interleukin-1 injection. Issue 1 (December 2016) - Bray, Natasha; Burrows, Fiona; Jones, Myles; Berwick, Jason; Allan, Stuart; Schiessl, Ingo
Abstract Background Neurovascular coupling describes the mechanism by which the energy and oxygen demand arising from neuronal activity is met by an increase in regional blood flow, known as the haemodynamic response. Interleukin 1 (IL-1) is a pro-inflammatory cytokine and an important mediator of neuronal injury, though mechanisms through which IL-1 exerts its effects in the brain are not fully understood. In this study, we set out to investigate if increased cerebral levels of IL-1 have a negative effect on the neurovascular coupling in the cortex in response to sensory stimulation. Methods We used two approaches to measure the neuronal activity and haemodynamic changes in the anaesthetised rat barrel somatosensory cortex in response to mechanical whisker stimulation, before and for 6 h after intra-striatal injection of interleukin-1β or vehicle. First, we used two-dimensional optical imaging spectroscopy (2D-OIS) to measure the size of the functional haemodynamic response, indicated by changes of oxyhaemoglobin (HbO2 ) and total haemoglobin (HbT) concentration. In the same animals, immunostaining of immunoglobulin G and SJC-positive extravasated neutrophils was used to confirm the pro-inflammatory effects of interleukin-1β (IL-1β). Second, to examine the functional coupling between neuronal activity and the haemodynamic response, we used a 'Clark-style' electrode combined with a single sharp electrode to simultaneously record local tissue oxygenation (partial pressure oxygen, pO2 ) in layer IV/V of the stimulated barrel cortex and multi-unit activity (MUA) together with local field potentials (LFPs), respectively. Results 2D-OIS data revealed that the size of the haemodynamic response to mechanical whisker stimulation declined over the 6 h following IL-1β injection whereas the vehicle group remained stable, significant differences being seen after 5 h. Moreover, the size of the transient increases of neuronal LFP activity in response to whisker stimulation decreased after IL-1β injection, significant changes compared to vehicle being seen for gamma-band activity after 1 h and beta-band activity after 3 h. The amplitude of the functional pO2 response similarly decreased after 3 h post-IL-1β injection, whereas IL-1β had no significant effect on the peak of whisker-stimulation-induced MUA. The stimulation-evoked increases in gamma power and pO2 correlated significantly throughout the 6 h in the vehicle group, but such a correlation was not observed in the IL-1β-injected group. Conclusions We conclude that intra-striatal IL-1β decouples cortical neuronal activity from its haemodynamic response. This finding may have implications for neurological conditions where IL-1β plays a part, especially those involving reductions in cerebral blood flow (such as stroke).